The Value of Diagnostic Laparoscopy in Gastroenterology (Due to 3000 cases) - Atilla ÖKTEN,; Süleyman YALÇIN,; Güngör BOZTAŞ,; Oktay YEĞİNSÜ,; Sadakat ÖZDİL,; Zeynel MUNGAN,; Yılmaz ÇAKALOĞLU,; Sebahattin KAYMAKOĞLU,; İlhan ULAGAY, (Turkish Journal of Gastroenterology, 2020)
-